The research progress of thrombospondin type-1 domain 7A and its antibodies in idiopathic membranous nephropathy - LI Jun; WANG Yan-yan; CHENG Hong (Linchuang shenzangbing zazhi)
Idiopathicmembranous nephropathy(IMN) is an autoimmune glomerular disease with unknown etiology. Current studies have shown that phospholipase A2 receptor(PLA2R) and thrombospondin type-1 domain 7 A(THSD7A) are closely related to the pathogenesis of IMN. At present, serum anti-PLA2R antibody detection and glomerular PLA2R antigen staining have been used for clinical diagnosis and prognosis, but the related detection of THSD7A has not been widely used in clinical practice. Therefore, this paper will review the current role and research progress of THSD7A in IMN.